PENGARUH PROMOSI, HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ALAT RUMAH TANGGA - Della Silvia (JURNAL EKOBIS DEWANTARA, 2022)
Abstract This study aims to determine the effect of promotion, price, product quality and brand image simultaneously or partially on purchasing decisions on household appliances at the Metro Campus in Solo Raya. The sampling technique used was quantitative methods, the population used in this study were all consumers who bought household appliances at the Metro Campus with a sample of 100 respondents. While the data analysis technique used is the multiple linear regression method. These results indicate that based on the t test, it can be seen that the promotion and price variables do not have a significant influence on purchasing decisions, while product quality and brand image have a significant and positive influence on purchasing decisions. Keywords: promotion, price, product quality and brand image.